The fetal hydrops–associated single-residue mutation L322P disrupts mechanical but not chemical activation of the PIEZO1 ion channel - Jinghui Jiang; Wei Guo; Xudong Chen; Qijing He; Yubo Wang; Xiaohui Zhu; Liying Yan; Jie Qiao; Bailong Xiao (Proceedings of the National Academy of Sciences, 2025)
The mechanically activated PIEZO1 ion channel is genetically linked to numerous physiological and pathophysiological processes. For example, deleting PIEZO1 in mice leads to defective lymphatic vessel development, while nonsense mutations in humans are associated with autosomal recessive generalized lymphatic dysplasia (GLD) and nonimmune hydrops fetalis. However, it remains unclear whether PIEZO1-dependent biological processes are directly mediated by its intrinsic mechanosensitivity. Here, we identified a human fetal hydrops–associated single-residue mutation, L322P (corresponding to L329P in mouse PIEZO1). The mutant failed to show mechanically activated currents in response to poking or stretch of the cell membrane, but preserved normal plasma membrane expression and responsiveness to its chemical activators such as Yoda1 and Jedi1. Remarkably, the mechanical response of the mutant can be restored by Yoda1. These findings demonstrate a direct link between the loss of PIEZO1’s mechanosensitivity and the pathophysiological phenotype of fetal hydrops and raise the therapeutic potential of using PIEZO1 chemical activators to restore the mechanosensitivity of PIEZO1 missense mutants that are associated with genetic diseases such as GLD and hydrops fetalis.